An Analysis of Code-Mixing Used by Gaby Hartanto in The Indah G Show YouTube Content - Tsurayya, Najwa Azhar; Octaviani, Nita Puji; Arochman, Taufik (Journal of English Teaching, Literature, and Applied Linguistics, 2025)
This research focuses on Gaby Hartanto's utterances in a podcast entitled 'Stigmas Against Models & The Unspoken Dark Side of Being Physically Attractive' on Indah G Show's YouTube channel. The study intends to analyze the types of code-mixing used by Hartanto and the factors that influence its use. The researchers used a descriptive qualitative method to collect data from a video transcript. The researchers applied Hoffman's theory, which categorizes code-mixing into different types, to analyze the data. The findings highlight how bilinguals apply code-mixing as both a linguistic function and a means of expressing identity, as well as the factors behind it. After analyzing Gaby Hartanto and Indah's podcast videos, the most common type of code-mixing used by Hartanto is insertion code-mixing, followed by alliteration and congruent lexicalization. The main factor influencing the use of code-mixing is talking about a particular topic; that is, the utterance is more accurate or relevant when explained in a foreign language.